The Effect of Social Media Marketing and Employee Service Quality on Purchase Itention: The Mediating Role of Customer Statisfication (Evidence from E-Wallet Users in North Sulawesi) - Rivaldo R. Rarumangkay; Lilly Linne Kainde (STIE Amkop Makassar, 2026)
Although social media marketing (SMM) and service quality have been widely examined in various digital service contexts, empirical insights regarding their role in shaping customer satisfaction and purchase intention in non-metropolitan fintech settings remain limited. This gap is particularly evident in the context of e-wallet users in North Sulawesi, where digital service adoption differs from metropolitan areas. Therefore, this study aims to address this gap by investigating the effects of SMM and Employee Service Quality (ESQ) on Purchase Intention (PI), with Customer Satisfaction (CS) as a mediating variable. A survey-based approach was employed using purposive sampling, and data from 115 e-wallet users were analyzed using SmartPLS. The empirical results show that SMM does not significantly influence CS or PI, indicating that social media exposure alone is insufficient to shape user satisfaction or behavioral intention. In contrast, ESQ demonstrates a strong and significant positive effect on CS, and CS is found to be a significant predictor of PI. Additionally, CS mediates the relationship between ESQ and PI, suggesting that service quality influences purchase intention primarily through satisfaction. However, no mediating effect is observed in the relationship between SMM and PI.These findings highlight the dominant role of service quality over social media marketing in driving satisfaction and continued e-wallet usage in non-metropolitan regions.